APLIKASI INTERAKTIF TAHFIDZ AL-QURAN JUZ AMMA (STUDI KASUS DI SDI MOHAMMAD HATTA) - Rahmat Solihin (As-Sibyan, 2020)
Tahfidz Al-Quran really needs to be taught at all levels of education, especially on early age as in the level of elementary school. Apart from the fact that the Al-Quran is a guidelife for all mankind, it is also because by memorizing the Al-Quran, students' intelligence and academic achievement can be improved. This study aims to find out how the implementation of the interactive application tahfidz juz amma in improving the student’s memorization quality of SDI Mohammad Hatta Malang. The method used in this study is a quantitative method with a total of 12 research subjects who are learning groups in Al-Quran learning which consists of V grade and VI grade students of SDI Mohammad Hatta Malang. The instruments of data collection used were learning test result, questionnaires, interviews and observation. Based on the results of the study, it is known the value of the t count = 3.450 and the value of t table = 2.201, this shows that 3,450 > 2,201. From this result it can be seen that the value of t count is greater than the value of t table, so it can be concluded in general that the interactive application of tahfidz juz amma is effective to help improving the quality of students memorization in tahfidz Al-Quran juz amma. While the attractiveness level of the application is at a very attractive level with an attractiveness level of 80%.